2019
DOI: 10.3791/58929
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Differentiation Model of Human Normal Memory B Cells to Long-lived Plasma Cells

Abstract: Plasma cells (PCs) secrete large amounts of antibodies and develop from B cells that have been activated. PCs are rare cells located in the bone marrow or mucosa and ensure humoral immunity. Due to their low frequency and location, the study of PCs is difficult in human. We reported a B to PC in vitro differentiation model using selected combinations of cytokines and activation molecules that allow to reproduce the sequential cell differentiation occurring in vivo. In this in vitro model, memory B cells (MBCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…We adopted an in vitro differentiation protocol of human peripheral B-cells to generate human ASCs ( 6 , 7 , 8 ). Isolated B-cells from healthy donors were stimulated with CpG for 1 day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopted an in vitro differentiation protocol of human peripheral B-cells to generate human ASCs ( 6 , 7 , 8 ). Isolated B-cells from healthy donors were stimulated with CpG for 1 day.…”
Section: Resultsmentioning
confidence: 99%
“…Human PCs only represent ∼0.25% of total bone marrow cells and these cells home to different tissues in the human body, making extensive molecular analysis and functional studies challenging ( 5 ). Protocols for in vitro differentiation of human peripheral B-cells into ASCs ( 6 , 7 , 8 ) form the basis for phenotypic and functional studies ( 9 , 10 ). Studies in mice have shown divergent gene expression profiles for the different Ig class PCs ( 11 ) and different expression profiles were observed comparing human class–switched germinal center B-cells from human tonsils as compared to nonclass–switched cells ( 12 ).…”
mentioning
confidence: 99%
“…The limited antibody secretion detected from plasmablasts following this in vitro stimulation points to a need to apply other approaches, such as single-cell BCR sequencing, to examine the antigen-specific plasmablast repertoire. Alternatively, this stimulation protocol could be modified to include factors essential for plasmablast/plasma cell survival and differentiation, such as IL-6, IL-10, IFN-α and APRIL ( 50 , 51 ). Such modifications would need to be separately tested for their impact on other B cell subsets.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted an in vitro differentiation protocol of human peripheral B-cells to generate human ASCs (6)(7)(8). Isolated B-cells from healthy donors were stimulated with CpG for 1 day.…”
Section: Phenotypic Multi-modal Single-cell Analysis Of Human Antibod...mentioning
confidence: 99%
“…Human PCs only represent ~0.25% of total bone marrow cells and home to different tissues in the human body, making extensive molecular analysis and functional studies challenging (5). Protocols for in vitro differentiation of human peripheral B-cells into ASCs (6)(7)(8) form the basis for phenotypic and functional studies (9,10). Studies in mice have shown divergent gene expression profiles for the different Ig class PCs (11) and different expression profiles were observed comparing human class-switched germinal center (GC) B-cells from human tonsils as compared to non-class switched cells (12).…”
Section: Main Text Introductionmentioning
confidence: 99%